Polyphonic federalism toward the protection of fundamental rights - Schapiro, Robert A. (Chicago, Ill. ; London : University of Chicago Press, 2009)
Here, Robert A. Schapiro defends the advantages of multiple perspectives in government, arguing that the resulting 'polyphony' creates a system that is more efficient, democratic and protective of liberties.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Federal government -- United States; Civil rights -- United States; Law; United States of America, USA; Politics & government; Constitution: government & the state; Constitutional & administrative law: general